THE EFFECT OF PAIR CHECK MODEL ON STUDENTS’ READING COMPREHENSION OF REPORT TEXT (A STUDY AT THE ELEVENTH GRADE STUDENTS OF SMKS TI PUTRA HARAPAN 2 IN 2020-2021 ACADEMIC YEAR) - Tiya Mawarni Ritonga Tiya Ritonga (JURNAL LINER (Language Intelligence and Educational Research), 2020)
ABSTRACT The aim of this research are to know: 1) the application of pair check model on teaching reading comprehension of report text, 2) the students reading comprehension of Report Text before and after pair check model, 3) Whether there is any significant effect of pair check model on teaching reading comprehension of report text at the Eleventh Grade Students of SMKS TI Putra Harapan 2. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research was all of the XI grade students’ of SMKS TI Putra Harapan 2 which consist of 67 students. Sample were XI TKJ which consist of 22 students which taken by purposive sampling. In collecting the data the researchers uses observation sheet and test as an instrument. The result of this research: 1) the application of pair check model was 3.4, categorized “Very Good”. 2) the mean score of the students’ reading comprehension of report text was 62.59 categorized “enough”. Meanwhile, after pair check model was 82.36, categorized “very good”. The result of data analysis shows that ttest was higher than ttable (ttest 25.23> ttable 2.08). So, the hypothesis was accepted. It means that, there is any significant effect of pair check model on students’ reading comprehension of report text at the XI grade students of SMKS TI Putra Harapan 2.